VeggieFruit Scoops: A feasibility study on vegetable fruit ice cream - Nhelmhar C. Basa, John Renald C. Esquivel, Francheska Reinge H. Lalu, Josephine Cassandra M. Pana, Janna Marie M. Sangalang 4 0 16; 5
u
Feasibility Study: (BSBA major Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2